Mediating Role of Competitive Advantage on the Relationship between AIS Implementation and SMEs Performance in Jordan: A Proposed Framework - ahmad (Ayassrah), Ahmad Y. A. Bani (International Journal of Psychosocial Rehabilitation, 2020)
The study undertakes an extensive review of Accounting Information System (AIS) literature through which it identified a gap on lack of comprehensive framework that integrate AIS, competitive advantage and SMEs performance in a single model. Therefore, through the support of Resource-based View (RBV) Theory, the study proposeda conceptual framework on the influence of AIS dimensions (AIS alignment and AIS sophistication) on the SMEs performance through the mediation effect of competitive advantage. The framework highlights that SME that implemented a well aligned and highly sophisticated AIS would likely gain more competitive advantage and will eventually outperformed SMEs which do not possess such technological attributes. The study not only highlights the need on the validation of the proposed framework for more reliable insights but also highlights the need for future studies to expand on this effort through the identification of other potential mediators within the continuum of AIS-Performance relationship from SMEs perspectives. This is possible considering consistent results in such as a relationship.